Ethical frameworks and ethical behavior: A survey of business students - Watts, Larry R. (International journal of value-based management, 1994)
This study investigated the efficacy of collegiate attempts to help students cope with ethical dilemmas. Data were collected from 674 business students on their ethical frameworks and ethical behaviors. Modest support was found for the relationship between the frameworks used for decision making and the choices made when confronted with an ethical dilemma. Furthermore, it was found that ethical frameworks were generally resistant to change over time while behavioral choices did change over time.